Predictive Power of Key Financial Variables During the Unconventional Monetary Policy Era - Kuosmanen, Petri; Vataja, Juuso (WILEY, 2025)
This study investigates the forecasting power of three well-established financial predictors during the prolonged era of unconventional monetary policy: the term spread, the short-term interest rate, and stock returns. The focus is on predicting GDP growth in both the United States and the Euro area. Our out-of-sample forecasting analysis specifically targets the period characterized by the short-term interest rate effectively bounded at or near the zero lower bound. We recognize that the information content of the term spread is likely to change under such circumstances. Similarly, the dynamics of the short-term interest rate could be altered due to unconventional monetary policy measures. To address this, we modify the short rate calculation by incorporating the shadow interest. This shadow interest rate can go much lower on the negative side than normal interest rates, making it a potentially more accurate rate to describe the monetary policy stance of central banks. The forecasting analysis covers the period from 2009:1 to 2022:3. Our results unambiguously reveal that the predictive power of the term spread completely vanishes during the zero lower bound era. Although the shadow rate has minor predictive content, the strongest predictor consistently lies in real stock returns during unconventional monetary policy. Our findings challenge the conventional wisdom and the stylized fact of the term spread as the most reliable financial predictor for economic activity. According to our results, this does not hold true under unconventional monetary policy, and using the shadow interest rate does not make a major difference in that respect. By shedding light on the changing dynamics during unconventional monetary policy, our study contributes novel insights to the existing literature.
Keywords: forecasting; macroeconomy; short-term interest rates; stock market; term spread; fi=Taloustiede|en=Economics|; fi=Taloustiede|en=Economics|